The forgotten population: the intersection of military-connected students and special education - Meritt, Nicole Marie (Kansas State University, 2023)
Military-connected students currently make up 1.3 million of K-12 students enrolled in public schools across the United States (US Department of Defense, 2020). There are also more than seven million students with an identified exceptionality qualifying them to receive special education services (National Center for Education Statistics, 2022). While states are required to collect data on enrollment of military-connected students, as well as the number of students receiving special education services, they do not collect data on how many military-connected students are also identified as exceptional. As a result, this unique population of students can be thought of as “the forgotten population” and the unique needs of this population are unclear. In this phenomenological qualitative study, the impact of military-related transitions on the educational experiences of a child with exceptionalities are explored. Four parents of military-connected children with exceptionalities engaged in qualitative interview and timeline elicitation. These qualitative data were coded and analyzed through the lens of ecological systems theory to identify the impacts of military-related transitions on the school experiences of a military-connected child with exceptionalities. Four key themes are identified and described. Through these themes, the experiences of the forgotten population are shared, and insight into their unique needs is provided. The first theme, out of compliance, describes the delays and discrepancies experienced by the participants’ children, resulting in the special education being out of legal compliance. The second theme, lack of understanding creates tension, discusses an overall lack of understanding of military culture by educators. The impact of this lack of understanding on the child’s school experiences is explored. The third theme, fear, anxiety, and stress describes the specific internal feelings of the child, their parent(s), and the resulting impact on school experiences. The fourth theme, advocating for child, discusses how each of the prior themes result in parents needing to advocate for their military-connected exceptional child.
Keywords: Military-connected students; Special education; Military-related transition